The effects of natural disasters on the labour market: Do hurricanes increase informality? - Camilo José Pecha Garzón (Inter-American Development Bank (IDB), 2017)
This paper studies the probability of formally employed men falling into informality because of exposure to hurricanes and tropical storms. It combines destruction variables calculated from historical storms' physical characteristics at the district level with 36 quarterly rounds of labour force surveys in Jamaica. The empirical strategy exploits variation arising from the storms' timing, intensity, and geographic locations within a panel random-effects endogenous choice model framework. Controlling for potential biases due to initial conditions, panel attrition, and employment selection, findings suggest that hurricanes do not affect unemployment and positively affect the transition to informality probability regardless of whether the individual was initially employed in a formal or an informal job. When the marginal effects of the storm were studied, the probability of becoming informally employed ranges between 8.5 and 14.5 per-cent depending on the employee's initial state and the moment when the storms were suffered. The effect is mainly driven by the impact of hurricanes on the service sector. These results suggest that the public and private policy agenda on adaptation to climate change should incorporate a discussion on how to off-set the negative effects of hurricanes, since these events could become worse in the near future.
Keywords: C33; E26; J01; J22; Q54; 330; Tropical storms; informal employment; labour market transitions; endogeneity; simulated based estimation; Jamaica